1991
DOI: 10.1136/gut.32.1.12
|View full text |Cite
|
Sign up to set email alerts
|

Sedation for upper gastrointestinal endoscopy: results of a nationwide survey.

Abstract: A postal questionnaire inquiring about routine sedation and premedication practice for upper gastrointestinal endoscopy was sent to 1048 doctors. Of 665 appropriate returns, 81% were from consultant physicians and surgeons. Most endoscopists (90%) reported using an intravenous benzodiazepine for at least three quarters of endoscopies and 54% of physicians and 69% of surgeons always did so. Midazolam was the intravenous sedative used by a third of ali respondents and 13% also used an additional intravenous agen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
90
0
10

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(103 citation statements)
references
References 9 publications
3
90
0
10
Order By: Relevance
“…The four deaths in this large cohort of patients occurred in patients with American Society of Anesthesiologists (ASA) [21] statuses of 3 or higher who were undergoing non-routine medical procedures, and three of the patients had serious underlying illnesses. These results indicate that the safety of propofol administration by endoscopists is comparable or superior to the published safety records of opioids and benzodiazepines administered by endoscopists for GI endoscopy [5][6][7][8]. The low incidence of complications may be attributed to new technologies such as computer-assisted personalized sedation.…”
mentioning
confidence: 61%
See 1 more Smart Citation
“…The four deaths in this large cohort of patients occurred in patients with American Society of Anesthesiologists (ASA) [21] statuses of 3 or higher who were undergoing non-routine medical procedures, and three of the patients had serious underlying illnesses. These results indicate that the safety of propofol administration by endoscopists is comparable or superior to the published safety records of opioids and benzodiazepines administered by endoscopists for GI endoscopy [5][6][7][8]. The low incidence of complications may be attributed to new technologies such as computer-assisted personalized sedation.…”
mentioning
confidence: 61%
“…The incidence of adverse events for these standard sedatives is very low [2,[5][6][7][8]. For instance, a large-scale retrospective study (21,011 patients) of midazolam for endoscopic sedation showed that the complication rate was only 1.35 % [2].…”
mentioning
confidence: 99%
“…However, the procedure is unpleasant, and still associated with a small but potential risk of complications [5] . In addition, it is often carried out with the patients under sedation, which may bring additional complications in patients with cirrhosis [6] .…”
Section: Introductionmentioning
confidence: 99%
“…The risk of the examina− tion or intervention depends primarily on the in− vasiveness and technical complexity of the pro− cedure, but also on the patient's individual risk profile and the specific side−effect profile of the sedatives or anesthetics used. The overall rate of serious complications in gastroenterological ex− aminations and interventions is between 1 in 1000 and 1 in 7500 [2]. The quality of procedures and, in turn, patient safety depend greatly on precise and careful risk estimation before, during, and after the proce− dure.…”
mentioning
confidence: 99%